Antimicrobial And Antioxidant Activity Of Methanol Extract Of Echinophora Spinosa L. From Jijel, Algeria - Ghadbane, Mouloud; Bounar, Rabaha; Rebbas, Khellaf (جامعة الوادي - University of Eloued, 2020)
In this study, the antioxidant and antimicrobial activities of Echinophora spinosa were investigated. Antimicrobial activity of methanol extracts obtained from Echinophora spinosa was examined using the disc diffusion method. Antioxidant activity of the methanol extracts was examined using the stable 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging test. Methanol extract of ripe fruits of E. spinosa showed highest total phenolic content (69.17 ± 1.2 μg GAE/mg extract) and the major flavonoid contents (12.122 ± 0.44 μg QE/mg extract) was found in leaves of the plant. In disk diffusion antimicrobial assay, E. spinosa manifested broad spectrum of activity. The largest capacity to neutralize DPPH radicals was found for ripe fruits methanol extract of E. spinosa plant. The results shows that the various parts of E. spinosa extracts promising antioxidant and antimicrobial activities have potential bioactivities due to high content of phenolic and flavonoid compounds.
Keywords: Antioxidant ; Echinophora spinosa ; Flavonoid ; methanol extracts; Antimicrobial